Properdin Is a Key Player in Lysis of Red Blood Cells and Complement Activation on Endothelial Cells in Hemolytic Anemias Caused by Complement Dysregulation - Chen, Jin Y.; Galwankar, Neeti S.; Emch, Heather N.; Menon, Smrithi S.; Cortes, Claudio; Thurman, Joshua M.; Merrill, Samuel A.; Brodsky, Robert A.; Ferreira, Viviana P. (Frontiers in Immunology, 2020)
The complement system alternative pathway (AP) can be activated excessively in inflammatory diseases, particularly when there is defective complement regulation. For instance, deficiency in complement regulators CD55 and CD59, leads to paroxysmal nocturnal hemoglobinuria (PNH), whereas Factor H mutations predispose to atypical hemolytic uremic syndrome (aHUS), both causing severe thrombohemolysis. Despite eculizumab being the treatment for these diseases, benefits vary considerably among patients. Understanding the molecular mechanisms involved in complement regulation is essential for developing new treatments. Properdin, the positive AP regulator, is essential for complement amplification by stabilizing enzymatic convertases. In this study, the role of properdin in red blood cell (RBC) lysis and endothelial cell opsonization in these AP-mediated diseases was addressed by developing in vitro assays using PNH patient RBCs and human primary endothelial cells, where the effects of inhibiting properdin, using novel monoclonal antibodies (MoAbs) that we generated and characterized, were compared to other complement inhibitors. In in vitro models of PNH, properdin inhibition prevented hemolysis of patient PNH type II and III RBCs more than inhibition of Factor B, C3, and C5 (>17-fold, or >81-fold, or >12-fold lower molar IC90 values, respectively). When tested in an in vitro aHUS hemolysis model, the anti-properdin MoAbs had 11-fold, and 86-fold lower molar IC90 values than inhibition of Factor B, or C3, respectively (P<0.0001). When comparing target/inhibitor ratios in all hemolysis assays, inhibiting properdin was at least as efficient as the other complement inhibitors in most cases. In addition, using in vitro endothelial cell assays, the data indicate a critical novel role for properdin in promoting complement activation on human endothelial cells exposed to heme (a hemolysis by-product) and rH19-20 (to inhibit Factor H cell-surface protection), as occurs in aHUS. Inhibition of properdin or C3 in this system significantly reduced C3 fragment deposition by 75%. Altogether, the data indicate properdin is key in promoting RBC lysis and complement activation on human endothelial cells, contributing to the understanding of PNH and aHUS pathogenesis. Further studies to determine therapeutic values of inhibiting properdin in complement-mediated diseases, in particular those that are characterized by AP dysregulation, are warranted.